Development of innovative modelling techniques for improving urban drainage design of high complexities - Lu, Wei (Nanyang Technological University, 2020)
An urban drainage system is one of the most critical urban infrastructures to accommodate extensive rainfall to avoid urban flood damages. However, the increasing climatic extremes and urbanization have challenged the existing drainage systems in many places with sufficient capacity to adapt to escalated frequency and severity of extreme rainfalls. This Ph.D. research topic focuses on exploring various novel modeling techniques, involving statistics, simulation, optimization, surrogate emulator, climate change impact assessment and uncertainty analysis to help achieve a trade-off between infrastructure investment and other conflicting objects such as flood resilience and rainwater retention. Previous studies conducted by other researchers are reviewed. Four major research works are presented. Some challenging issues are identified, and the related potential future works are proposed in achieving comprehensive and robust designs of urban drainage systems.